How Kan's response to empiricism uncovered the complex structure of human cognition: a phenomenological study of mental content - Vollet, Lucas (Kairós, 2024)
Restoring the epistemological foundation of natural science through the identification of the synthetic unity of modal and counterfactual representations – those that presume the necessary character of the restricting possibilities of the empirical world – was Kant’s principal goal in opposing Hume. But in order to do so, he had to significantly alter the empiricist theory of human cognitive capacity such that the idea of mind was no longer captured by a narrow definition of psychologism. Not only did he develop new explanations for synthetic or contentistic inferences (which were later technically developed by nonclassical intuitionistic logical theories), but he also advanced the philosophy of mind toward an idealized representation of mental structures by extending our psychological knowledge to complex theories about the correlation between a priori concepts and intuitions. We will outline Kant’s trajectory in this regard in the Critique of Pure Reason, including his absorption by Husserl’s phenomenology in the nineteenth century, and offer conclusions regarding how these theories anticipated semantic solutions on the content of intentionality and mental content.